THE INFLUENCE OF ORGANIZATIONAL CULTURE, WORK ENVIRONMENT, LEADERSHIP STYLE, EMPLOYEE COMPETENCE, AND MOTIVATION ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION IN STARBUCKS AND EXCELSO EMPLOYEES IN BATAM CITY - Fatma Tri Lestari; Evi Silvana Muchsinati (Politeknik Negeri Bengkalis, 2022)
This study aims to determine the effect of organizational culture, work environment, leadership style, employee competence, and motivation on employee performance through job satisfaction. The sample in this study was 60 Starbucks and Excelso employees in Batam City. Sampling in this study uses the saturation sampling method that uses the entire population as a sample. This research uses the application software Statistical Product and Service Solutions (SPSS) and Partial Least Square (PLS). The results showed that organizational culture on employee performance had no significant effect, work environment on employee performance had no significant effect, leadership style on employee performance through job satisfaction had a significant effect, competence on employee performance through job satisfaction had a significant effect, and motivation on employee performance. through job satisfaction significantly positive effect.